Efektifitas Kerja Peserta Magang Dalam Meningkatkan Minat Berwirausaha - Anisa Ikhsan; Roy Hasiru; Muchtar Ahmad (Universitas Negeri Gorontalo, 2021)
This research aimed to reveal the “work effectiveness of vocational students’ internships in increasing entrepreneurial interest in the Pia Putra Kusuma Gorontalo Company”, a case study of the on-the-job-training students at Putra Kusuma LKP. This study employed a qualitative descriptive method. The data collection techniques used in this study were observations, interviews, and documentation. It is revealed that: 1. The intern greatly aided the company in terms of office operation. 2. The interns were considered to be extremely helpful in the process of operational activities, starting from the production to the marketing stage, 3. The entrepreneurial interests of interns at LKP Pia Putra Kusuma are significantly diverse. It was shown that the interest in entrepreneurship manifested in a number of the interns.